2018
DOI: 10.1021/acs.energyfuels.7b03648
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Simultaneous Absorption and Desorption of CO2, SO2, and NOx Using Aqueous N-Methyldiethanolamine and Dimethyl Sulfoxide Solutions

Abstract: MDEA+DMSO aqueous solutions, made up of N-methyldiethanolamine (MDEA) and dimethyl sulfoxide (DMSO), were explored for the simultaneous absorption of CO2, SO2, and NO x . Experiments in a semibatch absorption–desorption system were carried out to measure the absorption and desorption performance of aqueous MDEA+DMSO solutions. The influences of concentration proportion, MDEA/DMSO concentration, absorption temperature, desorption temperature, and cycle index on the simultaneous absorption and desorption were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…It was found that methanol increased the CO 2 partitioning into the aqueous phase [33]. Additionally, it was reported that the addition of DMSO in a concentration range from 2.5 up to 3.3 M affected CO 2 absorption and increased the rate of CO 2 absorption in the presence of methyldiethanolamine [34]. However, our results obtained in the presence of ammonia did not show a rapid decrease in pH during CO 2 absorption in the DMSO solutions.…”
Section: The Course Of the Precipitationcontrasting
confidence: 66%
“…It was found that methanol increased the CO 2 partitioning into the aqueous phase [33]. Additionally, it was reported that the addition of DMSO in a concentration range from 2.5 up to 3.3 M affected CO 2 absorption and increased the rate of CO 2 absorption in the presence of methyldiethanolamine [34]. However, our results obtained in the presence of ammonia did not show a rapid decrease in pH during CO 2 absorption in the DMSO solutions.…”
Section: The Course Of the Precipitationcontrasting
confidence: 66%
“…[3][4][5] One efficient method for CO 2 capture is the use of aqueous alkanolamine solutions or their mixtures. 4,6,7 Monoethanolamine, diethanolamine, and N-methyldiethanolamine 8,9 are conventional chemical absorbents. 1,4,10,11 Piperazine is commonly used as a blend with other amines because its absorption capacity for CO 2 and absorption rate 7,8 are approximately twice than those of MEA and its energy requirements are approximately 15% less than those of MEA.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al (2017) and Wang et al (2016) were engaged in the research and development of high performance anhydrous oxide adsorption materials. Luo et al (2018) proposed a promising renewable absorbent for simultaneous removal of CO 2 /SO 2 /NOx, which made a foundation for following research in this field. and Wei et al (2015) were committed to the research of CO 2 capture technology for dry removal of flue gas by potassium-based absorbent.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) were engaged in the research and development of high performance anhydrous oxide adsorption materials. Luo et al. (2018) proposed a promising renewable absorbent for simultaneous removal of CO 2 /SO 2 /NOx, which made a foundation for following research in this field.…”
Section: Introductionmentioning
confidence: 99%